Continuous block-symmetric polynomials of degree at most two on the space (L_∞)^2 - Vasylyshyn, T.V. (Carpathian Mathematical Publications, 2016)
We introduce block-symmetric polynomials on (L_∞)^2 and prove that every continuous block-symmetric polynomial of degree at most two on (L_∞)^2 can be uniquely represented by some "elementary" block-symmetric polynomials.